KONTEKSTUALISASI KAIDAH DAR’U AL-MAFASID ‘ALA JALBI AL-MASHALIH DALAM MENANGKAL NARASI EKSTREMISME DI MEDIA SOSIAL - Anang Wahid Cahyono (CV. Lafadz Jaya, 2026)
Extremist narratives on social media have become a threat to social cohesion, tolerance, and religious moderation in Indonesia because digital platforms facilitate the rapid and widespread spread of propaganda, hate speech, takfirism, and identity polarization. This article contextualizes the principle of Dar’u al-Mafasid ‘Ala Jalbi al-Mashalih as a normative framework to prioritize the prevention of harm in the digital space when freedom of expression has the potential to give rise to public harm. This research uses a qualitative method based on literature review with a conceptual-normative approach, and links the principles of maqāṣid al-sharīʿah, sadd al-dharī’ah, and religious moderation as an analytical foundation. The results of the study indicate that these principles are relevant to underpin content moderation, information verification, digital literacy, and counter-narratives based on inclusive religious authority. Thus, Dar'u al-Mafasid not only functions as a classical principle, but also as an ethical-theological instrument for building a digital space that is safe, beneficial, and in line with the goals of religious protection and public benefit.